Comparative Study of External Beam Radiotherapy with Cisplatin Verses Paclitaxel in Locally Advanced Cervical Carcinoma - Shrestha, Suresh; Manandhar, Tara (Nepalese Journal of Cancer, 2018)
Objective: The purpose of the study was to identify the value and response of four field radiotherapy, combined with concurrent chemotherapy (cisplatin vs. paclitaxel) as radio a sensitizer.Method: Fifty patients with diagnosis of Carcinoma of Cervix were consecutively enrolled in this study 25 assigned in each group. Gr 1 was assigned for Cisplatin as sensitizer and Gr 2 received Paclitaxel. Radiation fields were similar. The response and adverse effects were evaluated in fixed interval or at the time when it occurred.Result: Fifty patients were enrolled. FIGO stage of disease were stage IIB (n=33) and stage IIIB (n=14). The most commonly used field size for anterior / posterior field 15 x 15 cm and 15 x 18 cm. The lateral field size from right and left are 15 x 7 cm and 15 x 6 cm. Cisplatin 30 mg /m2 or Paclitaxel 230mg/m2 were used as assigned in each group of 25. During weekly assessment of chemo-irradiation, the reaction was seen from second week to fifth week of the treatment which were mild to moderate in severity. Vesico-Vaginal Fistula were seen in 8.0% of patient. Eighteen patients came for one follow up, 15 patients attended two follow up, and 17 patients attended all three scheduled follow up. Complete response was evaluated in 25 patients (p=0.002), partial response in 14 patients (p=0.03) and poor response in 11 patients (P=0.50).Conclusion: There are no significant differences in cisplatin or paclitaxel as a sensitizer in concurrent radiotherapy in response for cancer of uterine cervix. Rate of side effects were also similar. Further large scale studies may evaluate the difference in response of concurrent chemo-radiotherapy of these two drugs to confirm the optimal duration and schedule of concurrent chemotherapy.